Testing For SARS‐CoV‐2: The Day the World Turned its Attention to the Clinical Laboratory - Xuemei Zhao; Julia F. Markensohn; David A. Wollensak; Omar F. Laterza (Wiley, 2020)
In the last few months, an unprecedented number of laboratory tests for coronavirus disease 2019 (COVID‐19) have been developed at a remarkable speed. With the rapid adoption of these tests into clinical practice, combined with the widespread publicity they received, questions arose related to the different types of tests, their utility, performance, and regulatory approval status. The aim of this publication is to provide a general landscape of laboratory testing for COVID‐19 and offer a historical and regulatory perspective associated with them. Specifically, we aim to elaborate on the regulatory complexities of diagnostic testing in the United States and its implications to the present outbreak, as well as provide a synopsis of laboratory tests that have been developed for COVID‐19. We will first address the detection of severe acute respiratory syndrome‐coronavirus 2 directly by either nucleic acid amplification tests or by the detection of the viral protein for active infections. Subsequently, we will provide an overview of serological tests that can aid not only in diagnosis but additionally help to identify prior infections and potential immunity.